Systematic Literature Review: Pengaruh Model Inquiry Learning terhadap Hasil Belajar IPA Siswa SMP - Efendi, Elvaretta; Ali, Eisa Putri; Asrizal, Asrizal; Mufit, Fatni (TSAQOFAH, 2025)
This study aims to analyze the impact of the Inquiry Learning model on improving junior high school students' learning outcomes in Natural Sciences (IPA) through a Systematic Literature Review (SLR) approach. Inquiry Learning is an innovative instructional model that emphasizes active student engagement in the learning process through exploration, investigation, and the discovery of concepts, both independently and collaboratively. This study collects and analyzes data from various journals, articles, and theses published within the last 10 years. The findings indicate that the Inquiry Learning model consistently has a positive impact on improving students' learning outcomes. The implementation of this model has been proven to enhance critical thinking skills, conceptual understanding, and students’ motivation to learn compared to conventional teaching methods. Factors such as the teacher’s role as a facilitator, the level of student engagement, and the support of the learning environment significantly contribute to the successful implementation of the Inquiry Learning model. Based on these findings, it is recommended that educators consider the broader application of the Inquiry Learning model to enhance the quality of science education at the junior high school level.